Effect of Coconut Shell Biochar Application on the Effectivity of NPK Fertilizer in Red Onion (Allium ascalonicum L.) Cultivation - Agata Desinta Yoanma; Agus Haryanto; Oktafri Oktafri; Sugeng Triyono (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Shallot cultivation in Lampung faces challenges because the land is dominated by ultisol soils, which have low nutrients. Therefore, soil improvement materials such as biochar and fertilizers are needed. This study aims to determine the effect of coconut shell biochar addition on the effectiveness of NPK fertilizer in the production of shallots. The study was arranged in a Factorial Completely Randomized Design consisting of 2 factors, namely the dose of biochar (0, 40, 80, and 120 g/pot) and the dose of NPK fertilizer (0, 0,8, 1,6, and 2,4 g/pot). Each treatment combination was repeated 3 times. Parameters included soil characteristics (pH, soil volume shrinkage) and plant parameters (plant height, number of leaves, canopy area, buld number and diameter, evapotranspiration, fresh root weight, bulb air dry weight, and water productivity. The results showed that coconut shell biochar had a significant effect (α = 0.05) in increasing soil pH and decreasing soil shrinkage. The dose of biochar 80 g/pot (B2) with a dose of NPK 1.6 g/pot (N3) was the best treatment. In this treatment combination, shallots produced an average weight of 120.54 g/pot of fresh stover, 14 bulbs with diameter of 2.05 cm and air dry bulb weight of 70.17 g/pot, and the water productivity of 18.22 kg/m3. Keyword: Canopy area, Fertilizer dose, pH, Soil shrinkage, Water productivity